PERAN DESIGNATED PERSON ASHORE (DPA) DALAM PENGOPERASIAN KAPAL YANG AMAN SESUAI KETENTUAN NASIONAL DAN INTERNASIONAL - Suganjar Suganjar; Renny Hermawati (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2019)
Safety management in the shipping industry is based on an international regulation. It is International Safety Management Code (ISM-Code) which is a translation of SOLAS ‘74 Chapter IX. It stated that the objectives of the Code are to ensure safety at sea, prevention of human injury or loss of life, and avoidance of damage to the environment, in particular, to the marine environment, and to property.it is also requires commitment from top management to implementation on both company and on board. The implementation of the ISM-Code is expected to make the ship’s safety is more secure. The ISM-Code fulfillment refers to 16 elements, there are; General; Safety and Environmental Protection Policy; Company Responsibility and Authority; Designated Person(s); Master Responsibility and Authority; Resources and Personnel; Shipboard Operation; Emergency Preparedness; Report and Analysis of Non-conformities, Accidents and Hazardous Occurrences; Maintenance of the Ship and Equipment; Documentation; Company Verification, Review, and Evaluation;  Certification and Periodical Verification; Interim Certification; Verification; Forms of Certificate. The responsibility and authority of Designated Person Ashore / DPA in a shipping company is regulated in the ISM-Code. So, it is expected that DPA can carry out its role well, than can minimize the level of accidents in each vessels owned/operated by each shipping company.Keywords : ISM Code, Safety management, Designated Person Ashore  Manajemen keselamatan di bidang pelayaran saat ini diimplementasikan dalam suatu peraturan internasional yaitu International Safety Management Code (ISM-Code) yang merupakan penjabaran dari SOLAS 74 Chapter IX-Management for the safe operation of ships. Tujuan dari ISM-Code “The objectives of the Code are to ensure safety at sea, prevention of human injury or loss of life, and avoidance of damage to the environment, in particular, to the marine environment, and to property” dan  ISM-Code menghendaki adanya komitmen dari manajemen tingkat puncak sampai pelaksanaan, baik di darat maupun di kapal.  Pemberlakuan ISM-Code tersebut diharapkan akan membuat keselamatan kapal menjadi lebih terjamin. Pemenuhan ISM-Code mengacu kepada 16 elemen yang terdiri dari ; umum; kebijakan keselamatan  dan perlindungan lingkungan; tanggung jawab dan wewenang perusahaan; petugas yang ditunjuk didarat; tanggung jawab dan wewenang nahkoda; sumber daya dan personil; pengopersian kapal; kesiapan menghadapi keadaan darurat; pelaporan dan analisis ketidaksesuaian, kecelakaan dan kejadian berbahaya; pemeliharaan kapal dan perlengkapan;  Dokumentasi; verifikasi, tinjauan ulang, dan evaluasi oleh perusahaan; sertifikasi dan verifikasi berkala; sertifikasi sementara; verifikasi; bentuk sertifikat. Tugas dan tanggungjawab Designated Person Ashore/DPA didalam suatu perusahaan pelayaran, telah diatur di dalam ISM-Code.  Sehingga diharapkan agar DPA dapat melaksanakan peranannya dengan baik, sehingga dapat menekan tingkat kecelakaan di setiap armada kapal yang dimiliki oleh setiap perusahaan pelayaran.Kata kunci : ISM Code, Manajemen keselamatan, Designated Person Ashore